2018 IEEE International Conference on Robotics and Biomimetics (ROBIO) 2018
DOI: 10.1109/robio.2018.8665209
|View full text |Cite
|
Sign up to set email alerts
|

On Internal Modeling of the Upright Postural Control in Elderly

Abstract: The second most common cause of injury in the elderly population is falling. In an effort to understand the mechanism behind the reduced ability to maintain balance in any posture or activity, we study the performance of the central nervous system as a controller of the body, while maintaining the balance in some postures or activities. Towards this direction, forty-five subjects aged over 70 were tested in different trials of quiet stance: a) hard stable surface with open eyes, b) stable surface with closed e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Despite this, force plate-based systems are highly unlikely to be utilized in home-based rehabilitation due to installation, cost and space related issues. Camera-based motion capture systems (i.e., Vicon) were utilized in three of the reviewed studies [ 22 , 25 , 36 ]. It was observed that camera-based systems are as impractical for a home-based rehabilitation setting as the force plate systems.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite this, force plate-based systems are highly unlikely to be utilized in home-based rehabilitation due to installation, cost and space related issues. Camera-based motion capture systems (i.e., Vicon) were utilized in three of the reviewed studies [ 22 , 25 , 36 ]. It was observed that camera-based systems are as impractical for a home-based rehabilitation setting as the force plate systems.…”
Section: Resultsmentioning
confidence: 99%
“…From the 23 reviewed papers, research was categorised into three key main purposes: (1) Understanding the underlying biological/anatomical functional causes creating disturbances in balance [ 24 , 32 , 34 , 36 ]; (2) identifying the falls or diagnosing balance issues [ 20 , 26 , 27 , 28 , 30 , 33 , 38 , 39 , 41 , 42 ]; and (3) identifying the factors (external or internal to a person) in order to predict when falls will happen [ 21 , 22 , 29 , 31 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to the best of our knowledge, there are few articles that have studied the controller of balance robotic applications based on human data. In [18], [19] we proposed a novel conceptual scheme for the modeling of the CNS in an upright posture that has been verified by human data and can be used as a controller of an inverted pendulum as the main model for most of the balance robotic applications. As an extension, in this work, we experimentally evaluate the proposed scheme with the following additional contributions.…”
Section: Introductionmentioning
confidence: 99%
“…One of musculoskeletal involvements for balance could be how different body segments participate in the adjustment in response to the body balance. It has been revealed that with multisensory feedbacks to the central nervous system (CNS) and sensorimotor control of CNS, leg and trunk segments could coordinate to maintain balance in different directions [4], angular excursions [5], and postures and activities [5,6]. During the time, body segments might response differently.…”
mentioning
confidence: 99%